Platelet-Rich Plasma and Platelet-Rich Fibrin Can Induce Apical Closure More Frequently Than Blood-Clot Revascularization for the Regeneration of Immature Permanent Teeth: A Meta-Analysis of Clinical Efficacy - Murray, Peter E. (Frontiers in Bioengineering and Biotechnology, 2018)
The purpose of this review was to compare the clinical efficacy of platelet-rich plasma (PRP) and platelet-rich fibrin (PRF), vs. blood clot revascularization (BCR) for the regeneration of immature permanent teeth. A survey of the literature identified 222 cases of immature permanent teeth which had been given PRP, PRF or BCR regeneration treatment with at least a year-long follow-up in 12 different articles. A meta-analysis of the 222 immature permanent teeth after 1 year, were compared to assess the ability of PRP, PRF, and BCR to accomplish apical closure, a periapical lesion healing response, root lengthening, and dentinal wall thickening. The mean success rate for apical closure or reduction after 1 year was: PRP (85.1%) PRF (85.2%), and BCR (58.8%). The mean success rate for root lengthening after 1 year was: BCR (64.1%), PRP (64.2%), and PRF (74.1%). The periapical lesion healing response was 88.9% for BCR, 100% for PRP, and 100% for PRF. Dentinal wall thickening was 100% for BCR, 100% for PRP, and 100% for PRF. Apical closure occurred more frequently following PRP and PRF than with BCR (Fischer test, P < 0.0011), for all the other effects the PRP, PRF, and BCR treatments were similarly effective (Fischer tests, P > 0.05). In conclusion, the fractured or decayed immature permanent teeth of children and young adults aged 6 years to 28 which have a restorable crown, but thin dentinal walls may be regenerated by using a revascularization procedure which draws blood and stem cells into a disinfected root canal space. Although BCR is most common revascularization method, apical closure may occur more frequently if PRF and PRP are used instead of BCR for the regeneration of immature permanent teeth. The proper use of regenerative procedures can be very successful at the disinfection of bacteria from the periapical region of immature permanent teeth, which helps to heal localized lesions, and avoid the need for complex apical surgery, in addition to regenerating tissues to strengthen the structure of immature teeth, to help prevent tooth fracture and tooth loss.